1993
DOI: 10.1007/bf00053148
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of the M-component immunoglobulin types of multiple myeloma

Abstract: The purpose of this population-based case-control study was to learn whether risk factors differ for the individual immunoglobulin types of multiple myeloma. In particular, we sought to determine whether IgA and IgG myeloma were related to a history of exposure to reported IgA- and IgG-stimulating conditions, respectively, or to a history of selected occupational and physicochemical exposures. The M-component immunoglobulin type was determined from immunoelectrophoresis as reported in medical records, and expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In total, 39 patients were included, representing the continuum from MGUS to SMM: 5 MGUS, 8 stage I, 5 stage II and 21 stage III MM patients. The distribution of Ig subtype in the patient population correlated well with previous studies [29], with a slight male gender bias of 1.2:1 for this cohort also being typical for MM reported cases internationally [30]. The considerably earlier average age of only 59.4 yrs (33-84 yrs range) compared to 69 was however unexpected [31].…”
Section: Links Between the Number Of Ctas Expressed And Disease Charasupporting
confidence: 86%
“…In total, 39 patients were included, representing the continuum from MGUS to SMM: 5 MGUS, 8 stage I, 5 stage II and 21 stage III MM patients. The distribution of Ig subtype in the patient population correlated well with previous studies [29], with a slight male gender bias of 1.2:1 for this cohort also being typical for MM reported cases internationally [30]. The considerably earlier average age of only 59.4 yrs (33-84 yrs range) compared to 69 was however unexpected [31].…”
Section: Links Between the Number Of Ctas Expressed And Disease Charasupporting
confidence: 86%
“…The expression of IgD or a biclonal paraprotein is observed in approximately 2% of the MM patients, while IgA is observed in approximately 22% of the MM patients (86–88). Petersen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IgD or a biclonal paraprotein is observed in approximately 2% of the MM patients, while IgA is observed in approximately 22% of the MM patients (86)(87)(88). Petersen et al found IgD paraprotein in 12% and IgA paraprotein in 28% of the 54 CNS MM patients, suggesting an overexpression of both IgA and IgD in CNS MM.…”
Section: Discussionmentioning
confidence: 99%
“…Farming as an occupation was associated with MM in studies from Canada, 29 New Zealand, 20,33 England, 23 the United States, 25,27 and Italy 44 (cultivation of apples and pears only). Brown et al 84 and Brownson and Reif 19 found no association between MM and farming in Iowa and Missouri, respectively.…”
Section: Multiple Myelomamentioning
confidence: 95%
“…The same group reported significant associations between "high" exposure to pesticides and both IgA and IgG lymphoma. 27 In an Italian study, 44 herbicides were not associated with MM but chlorinated insecticides and DDT were. A nested case-control mortality study 28 found that herbicide or insecticide exposures were not independent predictors but increased the statistically significant odds ratio related to farming.…”
Section: Multiple Myelomamentioning
confidence: 98%